Expression and the antigenicity of recombinant coat proteins of tungro viruses expressed in Escherichia coli - Yee, Siewfung; Chu, Chiahuay; Poili, Evenni; Magdline Sia, Henry Sum (Elsevier B.V., 2017)
Rice tungro disease (RTD) is a recurring disease affecting rice farming especially in the South and Southeast Asia. The disease is commonly diagnosed by visual observation of the symptoms on diseased plants in paddy fields and by polymerase chain reaction (PCR). However, visual observation is unreliable and PCR can be costly. High-throughput as well as relatively cheap detection methods are important for RTD management for screening large number of samples. Due to this, detection by serological assays such as immunoblotting assays and enzyme-linked immunosorbent assay are preferred. However, these serological assays are limited by lack of continuous supply of antibodies as reagents due to the difficulty in preparing sufficient purified virions as antigens. This study aimed to generate and evaluate the reactivity of the recombinant coat proteins of Rice tungro bacilliform virus (RTBV) and Rice tungro spherical virus (RTSV) as alternative antigens to generate antibodies. The genes encoding the coat proteins of both viruses, RTBV (CP), and RTSV (CP1, CP2 and CP3) were cloned and expressed as recombinant fusion proteins in Escherichia coli. All of the recombinant fusion proteins, with the exception of the recombinant fusion protein of the CP2 of RTSV, were reactive against our in-house anti-tungro rabbit serum. In conclusion, our study showed the potential use of the recombinant fusion coat proteins of the tungro viruses as alternative antigens for production of antibodies for diagnostic purposes.